Oral fluid/plasma cannabinoid ratios following controlled oral THC and smoked cannabis administration - Lee, Dayong (2013)
BACKGROUND: Oral fluid (OF) is a valuable biological alternative for clinical and forensic drug testing. Evaluating OF to plasma (OF/P) cannabinoid ratios provides important pharmacokinetic data on the disposition of drug and factors influencing partition between matrices. METHODS: Eleven chronic cannabis smokers resided on a closed research unit for 51 days. There were four 5-day sessions of 0, 30, 60, and 120 mg oral Δ(9)-tetrahydrocannabinol (THC)/per day followed by a 5-puff smoked cannabis challenge on Day 5. Each session was separated by 9 days ad-libitum cannabis smoking. OF and plasma specimens were analyzed for THC and metabolites. RESULTS: During ad-libitum smoking, OF/P THC ratios were high (median 6.1, range 0.2– 348.5) within 1 h after last smoking, decreasing to 0.1–20.7 (median 2.1) by 13.0–17.1 h. OF/P THC ratios also decreased during 5-days oral THC dosing, and after the smoked cannabis challenge, median OF/P THC ratios decreased from 1.4–5.5 (0.04–245.6) at 0.25 h to 0.12–0.17 (0.04–5.1) at 10.5 h post smoking. In other studies, longer exposure to more potent cannabis smoke and oromucosal cannabis spray was associated with increased OF/P THC peak ratios. Median OF/P 11-nor-9-carboxy-THC (THCCOOH) ratios were 0.3–2.5 (range 0.1–14.7) ng/µg, much more consistent in various dosing conditions over time. CONCLUSIONS: OF/P THC, but not THCCOOH, ratios were significantly influenced by oral cavity contamination after smoking or oromucosal spray of cannabinoid products, followed by time-dependent decreases. Establishing relationships between OF and plasma cannabinoid concentrations is essential for making inferences of impairment or other clinical outcomes from OF concentrations.